2015
DOI: 10.1371/journal.pone.0123012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Carer Support Needs Assessment Tool (CSNAT) in Community Palliative Care Using a Stepped Wedge Cluster Trial

Abstract: Family caregiving towards the end-of-life entails considerable emotional, social, financial and physical costs for caregivers. Evidence suggests that good support can improve caregiver psychological outcomes. The primary aim of this study was to investigate the impact of using the carer support needs assessment tool (CSNAT), as an intervention to identify and address support needs in end of life home care, on family caregiver outcomes. A stepped wedge design was used to trial the CSNAT intervention in three ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
1
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 30 publications
(31 reference statements)
8
114
1
20
Order By: Relevance
“…Consistent with this perspective, most of the CSNAT items relating to enabling the carer to care were either rated less highly or stayed the same when rated for the second time (Figure ). However, items addressing the carers’ health more directly (such as dealing with carers’ feelings and worries, looking after your own health and needing practical help in the home) were rated more highly at the second visit, which could be a reflection of the recognition by carers that their own needs have become more visible and acknowledged now due to the CSNAT, thus feeling that such requests are more legitimised, as reported in previous similar studies (Aoun, Deas, et al., ; Aoun, Grande, et al., ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Consistent with this perspective, most of the CSNAT items relating to enabling the carer to care were either rated less highly or stayed the same when rated for the second time (Figure ). However, items addressing the carers’ health more directly (such as dealing with carers’ feelings and worries, looking after your own health and needing practical help in the home) were rated more highly at the second visit, which could be a reflection of the recognition by carers that their own needs have become more visible and acknowledged now due to the CSNAT, thus feeling that such requests are more legitimised, as reported in previous similar studies (Aoun, Deas, et al., ; Aoun, Grande, et al., ).…”
Section: Discussionsupporting
confidence: 64%
“…In this study, four of five top carer priorities related to direct support for carers rather than support to directly enable care‐giving. In general, services are geared to providing for clients’/patients’ needs and carers’ needs tend to be overlooked (Aoun, Deas, et al., ; Aoun, Grande, et al., ; Ewing et al., ; Turner et al., ). Consistent with this perspective, most of the CSNAT items relating to enabling the carer to care were either rated less highly or stayed the same when rated for the second time (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, using the CSNAT intervention involves a change in practice from a practitioner‐led to a carer‐led process of assessment and support, and thus aligns with government policy and national guidelines for carer assessment and support, and recommendations for person‐centered practice (Department of Health [DoH], ; DoH, ; National Institute for Clinical Excellence, ; NHS Scotland, ; National Palliative and End of Life Care Partnership, ). Research on the CSNAT intervention has shown that it improves outcomes for carers (Aoun, Grande et al., ; Grande, Austin, Ewing, O'leary, & Roberts, ) is valued by carers (Aoun, Deas et al., ), and that practitioners feel it has benefits for their practice (Ewing, Austin, & Grande, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies included in the review found effects of an intervention with a needs-assessment (Aoun et al, 2015), the Carer Support Needs Assessment Tool (CSNAT) which is a valid tool to measure the support needs of family caregivers in palliative home care. (Aoun et al, 2015;Ewing, Austin, Diffin, & Grande, 2015). Our intervention is based on this CSNAT.…”
Section: Interventionmentioning
confidence: 99%